FRI0080 Effects of IL-6 Receptor Inhibition Therapy on The Serum Levels of IL-33 and IL-6 in Patients with Rheumatoid Arthritis. (15th July 2016) - Choi, I.A.; Lee, S.J.; Park, W.; Park, S.H.; Shim, S.-C.; Baek, H.J.; Yoo, D.-H.; Kim, H.A.; Lee, S.K.; Lee, Y.J.; Park, Y.E.; Cha, H.-S.; et al.
Abstract : Background: Several pro-inflammatory cytokines such as TNF-α, IL-1, IL-6, IL-8 and IL-15 are known to be critical in synovial inflammatory process in RA and successful results have been obtained in RA treatment with targeting pro-inflammatory cytokines including TNF-α, IL-1 and IL-6. Objectives: This study sought to investigate the role of IL-33 and IL-6 in RA patients receiving IL-6 receptor inhibition therapy. Methods: We analyzed the association of the IL-33 and IL-6 level with disease activity and serologic features in 83 patients with RA. We also measured the serum level of IL-33 and IL-6 before and after the administration of tocilizumab for 24 weeks in 40 patients. Results: Serum IL-33 level showed significant correlation with RF (rho =0.660, p<0.001) but did not correlate with DAS28, ESR, hsCRP or RA duration. IL-6 level was significantly correlated with hsCRP (rho =0.482, p<0.001) but not correlate with DAS28, ESR, RF or RA duration. There was no correlation between serum IL-6 and IL-33 levels. Serum IL-33 level significantly decreased after 24 weeks of IL-6 receptor inhibition in patients with RA (p<0.001). When comparing subgroups according to ACR20 response, serum IL-33 levels were significantly decreased after 24 weeks of IL-6 receptor inhibition therapy in ACR20 responders (p<0.001) but not in the non-responders (p=0.084). Baseline IL-33 levels were not significantly different between the two subgroups (p=0.765). Serum IL-6 levels were not significantly changed after 24 weeks of IL-6 receptor inhibition therapy (median 7.1 to 8.9 pg/mL, p=0.503). Changes of IL-6 levels were insignificant both in ACR20 responders and non-responders after 24 weeks of IL-6 receptor inhibition therapy. Baseline IL-6 levels were not different between ACR20 responders and non-responders. Conclusions: The use of IL-6 receptor inhibitor decreased the serum level of IL-33 and this effect seems to be led by the responder group. IL-33 could be a useful indicator to monitor the response in IL-6 receptor inhibition therapy. Disclosure of Interest: None declared